Dampak Pandemi COVID-19 pada Usaha Rumah Tangga dan Strategi Bertahan - Endah Marendah Ratnaningtyas; Jumadi Jumadi; Aftoni Sutanto (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2022)
MSMEs in Indonesia have good resilience in every crisis. However, the COVID-19 crisis has changed people's behavior and it is stated that they have not been able to overcome economic difficulties. This study aims to determine the impact of the COVID-19 pandemic on household businesses and survival strategies. This study uses a quantitative descriptive analysis method and uses respondent data as many as 54 people who are business actors in the production of processed food. Sources of data used in this study are primary data and secondary data. Methods of data collection using questionnaires and interviews. The data analysis technique used descriptive analysis technique. The results of this study are the impact of the COVID-19 pandemic crisis on business operations, strategies to survive in times of crisis, and obstacles in implementing strategies, as well as the benefits of social assistance from the government for business actors.